Hubungan Konsumsi Makanan Bergizi dengan Prestasi Belajar Anak - Mamahit, Adi Yeremia (Olympus : Jurnal Pendidikan Kesehatan dan Rekreasi, 2025)
This study aims to analyze the effect of nutritional adequacy through the Free Nutritious Food (MBG) program on the academic achievement of elementary school children in Tumani Village, South Minahasa. The study used a cross-sectional design with a sample of 30 students from grades 4-6 who had participated in the MBG program for at least 6 months. The independent variable was nutritional adequacy (adequate/inadequate) based on the balanced nutrition standards from the Indonesian Ministry of Health, while the dependent variable was academic achievement categorized as high or low based on report card scores. Data were analyzed using the chi-square test with a significance level of 0.05. The results showed a significant association between nutritional adequacy and students’ academic achievement (p=0.010). Students with adequate nutrition tended to have higher academic performance compared to those with inadequate nutrition. The MBG program proved effective in improving nutritional status and academic outcomes, thus it is recommended to be optimized and expanded in rural areas. These findings reinforce the importance of proper nutrition as a key factor in enhancing education quality and human resource development.